An integrated look into the Philippine Film Industry : the form, zoonomy, technology and its future a foresight study using scenario building - Cruz, Nidez S.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, Technology Management Center, 2017)
The local film industry was thriving. Filipino film productions dominated the screens. However, in the past two decades, the industry has experienced decline despite the introduction of digital film technologies that were supposed to make the film production process efficient and effective.
Several factors have been identified which led to where the industry stands today : economy, competition and absence of government policies to protect the industry, among others.
In the late 90's, Hollywood brought the industry to the next level. High-budgeted films won over audiences including the Filipinos. They're able to optimize technologies available to expand their borders. The local industry was caught off guard and during this period causing major production companies to struggle. From 200 films produced every year until mid 90's, it decreased to 60 in 2000's.
This did not stop film producers and filmmakers from producing their craft. With the available technologies related to filmmaking, many tried to play in the gaps in hopes to recapture lost market. These were the independent film companies, also known as indies, that have beer creating traction since the decline of Philippine cinema.
Today, there's an indication of recovery but the game has become more complex. More variables are involved and to be taken into account-this includes technology, society, value chains and other factors that would require assessment and management.
This research gives a glimpse to the future of Philippine film industry by integrating the form, economy and technology to look into different scenarios, short and long-term.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Film industry -- Philippines; Motion picture industry -- Philippines